Financial Accounting, Volume 1, First Part - Valix, Conrado T.; Peralta, Jose F. ; Valix, Christian Aris M. (Manila, 2017)
Volume One is in conformity with the undergraduate course syllabus for Financial Accounting I as promulgated by the Commission on Higher Education through the recommendation of the Board of Accountancy
Keywords: Accounting - Financial